PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Kasus Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018) - Violla Yumitri; Raja Adri Satriawan Surya; Arumega Zarefar (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
This study aims to examine the effect of corporate governance mechanisms on company performance. The corporate governance mechanism examined in this study includes internal governance consisting of: the board of commissioners and managerial ownership as well as foreign ownership, debt financing and audit quality. The population in this study are companies listed on the Indonesia Stock Exchange for the period 2015-2018. The sample in this research was determined by the purposive sampling method with a total sample of 103 company annual reports. Statistical test results show that the board of commissioners, managerial ownership, foreign ownership, debt financing has no influence on company performance while audit quality has an influence on company performance.